2017
DOI: 10.25115/psye.v9i2.698
|View full text |Cite
|
Sign up to set email alerts
|

Factors that promote or hinder physical activity participation in patients with colorectal cancer: A systematic review

Abstract: Different studies of patients with colorectal cancer have shown that physical activity has positive physical and psychosocial effects. However, most patients do not comply with the recommended criteria of physical activity. The aim of the present study was to analyze, by means of a systematic review of the literature, the factors associated with physical activity participation in patients with colorectal cancer. For this purpose, we conducted a search in the databases WEB OF SCIENCE, SCOPUS and SPORTDISCUS up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(87 reference statements)
1
2
0
Order By: Relevance
“…Despite this, the current review identified that lack of time resulted in the inability for healthcare professionals to promote physical activity. Current evidence supports the safety of physical activity for cancer patients across all treatment stages [7]; however, consistent with previous literature exploring barriers to and facilitators of physical activity participation [17][18][19], fear of causing harm by being physically active was identified as a barrier in the current review. Additional fears not cited across previous reviews included fear of judgment [35,38,54], fear of germs or infection [42], fear of nausea [39], fear of fainting [39] and fear of the unknown [39].…”
Section: Comparison With Previous Literaturesupporting
confidence: 79%
See 1 more Smart Citation
“…Despite this, the current review identified that lack of time resulted in the inability for healthcare professionals to promote physical activity. Current evidence supports the safety of physical activity for cancer patients across all treatment stages [7]; however, consistent with previous literature exploring barriers to and facilitators of physical activity participation [17][18][19], fear of causing harm by being physically active was identified as a barrier in the current review. Additional fears not cited across previous reviews included fear of judgment [35,38,54], fear of germs or infection [42], fear of nausea [39], fear of fainting [39] and fear of the unknown [39].…”
Section: Comparison With Previous Literaturesupporting
confidence: 79%
“…Using behaviour change theory to systematically identify barriers to and facilitators of physical activity in patients living with and beyond cancer may help to understand the determinants that influence physical activity promotion and behaviour. There have been previous systematic reviews that have explored barriers to and facilitators of physical activity in patients with cancer [16][17][18][19]. However, none of these reviews have used behaviour change theory to explore barriers and facilitators, or to understand and apply findings to physical activity promotion and practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the participant's personal preference and previous experience in sport participation should be taken into consideration when prescribing sport programs. [118][119][120][121] Third, a separate familiarization period before regular sport participation may be required for participants to learn and acquire the necessary skills related to the subsequent sport program, which should also be regarded as an indispensable part of a sport program to further ensure safety and maintain the participant's playing interest and enjoyment as well as facilitate exercise continuance. Finally, in order to increase the participation rate of cancer patients in a sport program, the prevalence of different sport events within a region and availability of facilities should be considered.…”
Section: Additional Considerationsmentioning
confidence: 99%